The long noncoding RNA lnc-HLX-2-7 is oncogenic in Group 3 medulloblastomas. Issue 4 (17th October 2020) - Katsushima, Keisuke; Lee, Bongyong; Kunhiraman, Haritha; Zhong, Cuncong; Murad, Rabi; Yin, Jun; Liu, Ben; Garancher, Alexandra; Gonzalez-Gomez, Ignacio; Monforte, Hector L; Stapleton, Stacie; Vibhakar, Rajeev; et al.
Abstract: Background: Medulloblastoma (MB) is an aggressive brain tumor that predominantly affects children. Recent high-throughput sequencing studies suggest that the noncoding RNA genome, in particular long noncoding RNAs (lncRNAs), contributes to MB subgrouping. Here we report the identification of a novel lncRNA, lnc-HLX-2-7, as a potential molecular marker and therapeutic target in Group 3 MBs. Methods: Publicly available RNA sequencing (RNA-seq) data from 175 MB patients were interrogated to identify lncRNAs that differentiate between MB subgroups. After characterizing a subset of differentially expressed lncRNAs in vitro and in vivo, lnc-HLX-2-7 was deleted by CRISPR/Cas9 in the MB cell line. Intracranial injected tumors were further characterized by bulk and single-cell RNA-seq. Results: Lnc-HLX-2-7 is highly upregulated in Group 3 MB cell lines, patient-derived xenografts, and primary MBs compared with other MB subgroups as assessed by quantitative real-time, RNA-seq, and RNA fluorescence in situ hybridization. Depletion of lnc-HLX-2-7 significantly reduced cell proliferation and 3D colony formation and induced apoptosis. Lnc-HLX-2-7 –deleted cells injected into mouse cerebellums produced smaller tumors than those derived from parental cells. Pathway analysis revealed that lnc-HLX-2-7 modulated oxidative phosphorylation, mitochondrial dysfunction, and sirtuin signaling pathways. The MYC oncogene regulated lnc-HLX-2-7, and the small-molecule bromodomain and extraterminal domain family‒bromodomain 4 inhibitor Jun Qi 1 (JQ1) reduced lnc-HLX-2-7 expression. Conclusions: Lnc-HLX-2-7 is oncogenic in MB and represents a promising novel molecular marker and a potential therapeutic target in Group 3 MBs.